2009
DOI: 10.1093/geront/gnp027
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Stay? Job Tenure Among Certified Nursing Assistants in Nursing Homes

Abstract: This study underscores the importance of the basic economics of job choice by low-income workers. Wages, fringe benefits, job security, and alternative choices of employment are important determinants of job tenure that should be addressed, in addition to training and organizational culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 23 publications
0
65
0
Order By: Relevance
“…In this descriptive analysis, immigrants appear to have a slightly longer tenure at the facility than non-immigrant CNAs. In a multivariate analysis, however, Wiener, Squillace, Anderson, and Khatutsky (2009) found that, after controlling for demographic and work-related factors, there was no statistically significant difference by immigration status in job tenure among all CNAs, but among CNAs with more than 1 year working at the facility, immigrants had shorter lengths of time on the job.…”
Section: Discussionmentioning
confidence: 84%
“…In this descriptive analysis, immigrants appear to have a slightly longer tenure at the facility than non-immigrant CNAs. In a multivariate analysis, however, Wiener, Squillace, Anderson, and Khatutsky (2009) found that, after controlling for demographic and work-related factors, there was no statistically significant difference by immigration status in job tenure among all CNAs, but among CNAs with more than 1 year working at the facility, immigrants had shorter lengths of time on the job.…”
Section: Discussionmentioning
confidence: 84%
“…Only 4 of the 188 worked in non-residential settings; three of these were home hospice workers. Respondents had solid NH experience, averaging 11 years in long-term care and almost 7 years in the current position; this tenure is substantially higher than that reported for NAs nationally32. Almost half the sample lived in small towns, a third, in large cities.…”
Section: Methodsmentioning
confidence: 87%
“…The group resembled NAs nationwide31, 32 in that they were predominantly female, in their mid-30s and high-school educated. Only 4 of the 188 worked in non-residential settings; three of these were home hospice workers.…”
Section: Methodsmentioning
confidence: 94%
“…Variables derived from the Area Resource File, Online Survey Certification and Reporting (OSCAR), and Minimum Data Set (MDS) were merged with the nursing home survey. Previous work on retention and turnover of CNAs indicates that important covariates are for-profit status, chain status, small facility size, large facility size, occupancy rate, location of facility in a metropolitan county, percent of residents with Medicaid, number of NHAs the nursing home has had in the past year, unemployment, registered nurse (RN) hours per day per resident, licensed practical nurse (LPN) hours per day per resident, CNA hours per day per resident, county nursing home beds, and county home health agencies (Banaszak-Holl & Hines, 1996; Castle & Engberg, 2005; Donoghue & Castle, 2007; Kash, Castle, Naufal, & Hawes, 2006; Kostiwa & Meeks, 2009; Probst et al, 2010; Wiener, Squillance, Anderson, & Khatutsky, 2009). Measures of staffing hours per resident per day were calculated from nursing home staffing data from OSCAR, described elsewhere (Tyler et al, 2013).…”
Section: Methodsmentioning
confidence: 99%